Influence of the Demultiplexer on Channel-Interleaved Photonic Analog-to-Digital Converters - Na Qian; Lei Yu; Jianping Chen; Weiwen Zou (IEEE Photonics Journal)
We investigate the demultiplexer in channel-interleaved photonic analog-to-digital converter (CI- PADC) and its influence on the performance of CI- PADC system by frequency domain modeling. The theoretical analysis reveals that the output power of the signal in different frequency sections is affected by the demultiplexer in different degrees. Subsequently, a method based on the derived figure of merit (FoM) is proposed to quantitatively evaluate and effectively minimize the impact of the demultiplexer on the signal in different frequency sections. According to the theoretical analysis, a CI- PADC system demultiplexed via dual-output Mach-Zehnder modulators is implemented to study and optimize the influence of demultiplexer. The experimental results with a flat frequency response in the range of 20 GHz verify the feasibility of the proposed method.